Should clinicians be allowed to accept gifts/honoraria/consulting fees from anyone? - Richardson, Kayla; Crossley, Emily (Translation: The University of Toledo Journal of Medical Sciences, 2025)
Should clinicians be allowed to accept gifts/honoraria/consulting fees from anyone? What would be lost if physicians could not work with such companies? What would be gained? Please write an essay focused on this dilemma. Be sure to consider the patient we saw in class with a DBS device who was doing very well, as well as the patient with opiate use disorder who had suffered considerably (keep in mind big pharma made the opiate epidemic worse with Oxytocin).